Pseudocyst forms of Trichomonas vaginalis from cervical neoplasia - Afzan, M.Y.; Suresh, K. (Springer Verlag (Germany), 2012)
Trichomonas vaginalis, a flagellated protozoan parasite causes a variety of adverse health consequences in both men and women. The parasite exists in the trophozoite and the pseudocystic stage. The study reports for the first time that pseudocyst forms of T. vaginalis isolated from cervical neoplasia (CN) patients demonstrated distinct, different and significant in vitro growth profiles when grown in vitro cultures from day 1 up to day 5 (p < 0.05, Mann-Whitney test) when compared with the same life cycle stages isolated from non-cervical neoplasia but symptomatic patients (NCN). Pseudocysts from CN and NCN isolates remained viable in distilled water until 3 h 10 min and 2 h 10 min, respectively. The nucleus of pseudocysts in CN isolates using acridine orange and DAPI showed more intense staining revealing higher nuclear content. The FITC-labeled Concanavalin A stained stronger green fluorescence with surface of pseudocysts in CN isolates showing more rough and creased surface with higher numbers of deep micropores with larger numbers of chromatin masses, vacuoles, and hydrogenosomes. The study confirms that pseudocystic stage from CN, despite the uniformity in appearance of being rounded and showing no motility without a true cyst wall under light microscopy, demonstrated different biochemical, surface, and ultrastructural properties. The study provides evidence that phenotypic variant forms of pseudocysts does exist and possibly does play a role in exacerbating cervical cancer.